Factors affecting Thai workers' use of hearing protection - Tantranont K. (2014)
This study used an ecological model to examine Thai workers' beliefs and attitudes toward using occupational hearing protection. Data collection involved focus group sessions with 28 noise-exposed workers at four factories in Chiang Mai Province and an interview with a safety officer at each organization. Detailed content analysis resulted in the identification of three types of factors influencing the use of hearing protection: intrapersonal, including preventing impaired hearing, noise annoyance, personal discomfort, and interference with communication; interpersonal, including coworker modeling, supervisor support, and supervisor modeling; and organizational, including organizational rules and regulations, provision of hearing protection devices, dissemination of knowledge and information, noise monitoring, and hearing testing. Effective hearing protection programs depend on knowledge of all of these factors. Strategies to promote workers' use of hearing protection should include the complete range of factors having the potential to affect workers' hearing.